Pregnancy and birth planning during COVID-19: The effects of tele-education offered to pregnant women on prenatal distress and pregnancy-related anxiety (vol 92, 102877, 2021) - Aksoy Derya, Yesim; Altiparmak, Sumeyye; Akca, Emine; Gokbulut, Nilay; Yilmaz, Ayse Nur (Elsevier Sci Ltd, 2021)
[Abstract Not Available]